Human Resource Transformation Opportunities Towards a Golden Indonesia 2045 - Nurhasanah; Sugeng Karyadi; Betty Rahayu; Nirmadarningsih Hiya; Eka Kurnia Saputra (Indonesian Journal of Business Analytics, 2026)
Human resource transformation is the most crucial pillar in realizing the vision of Golden Indonesia 2045, as this momentum coincides with the peak of the demographic bonus, which must be converted into a competitive advantage on a global scale. The purpose of this study is to provide an explanation of human resource transformation opportunities towards a Golden Indonesia 2045. This research is presented using a qualitative and descriptive approach. These qualitative and descriptive approaches are supported by secondary data such as books and journals. The results show that human resource transformation is the first pillar of the Golden Indonesia 2045 vision. With the goal of becoming one of the world's five largest economic powers, Indonesia can no longer rely solely on natural resources but must shift to an innovation and knowledge based economy. These opportunities include leveraging the demographic bonus, digital transformation and the gig economy, industrial downstreaming and the absorption of specialized labor, and reform of the education and vocational systems.